Expression of MicroRNAs and Its Regulation in Plants - Xie, Zhixin (2010)
MicroRNAs (miRNAs) have emerged as an essential regulatory component in plants. Many of the known miRNAs are evolutionarily conserved across diverse plant species and function in the regulatory control of fundamentally important biological processes such as developmental timing, patterning, and response to environmental changes. Expression of miRNAs in plants involves transcription from MIRNA loci by RNA polymerase II (pol II), multi-step processing of the primary transcripts by the DICER-LIKE1 (DCL1) complex, and formation of effector complexes consisting of mature miRNAs and ARGONAUTE (AGO) family proteins. In this short review, we present the most recent advances in our understanding of the molecular machinery as well as the regulatory mechanisms involved in the expression of miRNAs in plants.